Lung Vessel Morphological Structure - Kattakhodjaeva Dinara Utkurkhodjaevna; Gaipov Dilmurod Abdurasulovich; Sararbaeva Zhursinoy Sarsenbaevna; Akhmadjonov Abbosbek Akbaralievich (Zien Journals, 2023)
Purpose of the study: to study pulmonary arteries morphological structure. Materials and methods. For the experiment, 60 white outbred laboratory rats, weighing 220-280 grams, male aged 4-5 months were used. The structure of the pulmonary arteries layers and their morphometry were studied
Keywords: pulmonary arteries; arteries; postnatal ontogenesis